Role of tourism marketing in Tourism movement in Lattakia Governorate - لميس ناصر (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The tourism section is an important economic source which needs an interest and development because of decreasing tourism movement in Lattakia Governorate. It must make a plan to development this section internally and externally. It is a main factor in tourist promotion. A study of goals components and benefits of tourism marketing was done. A study of tourism marketing methods in Lattakia, and analyzing show and tourism movement was completed. In addition to study seasonal changcs of tourism movement, a study of tourism marketing and its effect on attractions in Lattakia Governorate was done. The study has showed that 80% of tourists have attractived by means of tourism marketing in Lattakia. The percent of domestic tourism in Lattakia reached 95% of total tourism movement in year 2018, and media consists 44% of tourism marketing means.